Structure and tree composition on the tropical dry forest in Sancán valley, Manabí, Ecuador - Wagner Ramírez Huila; Narcisa Elizabeth Ayoví Garces (Revista Cubana de Ciencias Forestales, 2022)
The tropical dry forest is a forest formation that requires greater knowledge of its dynamics and structure for management and conservation. In order to generate information on a dry forest remnant of the Sancán area, the floristic composition and structure of this was evaluated. Six sampling parcels settled down with a surface of 1 000 m2 (20 × 50 m); the diameter (D1.30) and height of all individuals e" 5 cm were recorded. Floristic composition, Shannon and Simpson index, abundance, frequency, dominance and importance value index were determined; and diametric structure was calculated. A total of 236 individuals, 21 species within 20 genera in 14 families were recorder. The families with the highest number of species were: Fabaceae, Malvaceae and, Euphorbiaceae; the most ecologically important species were: Ceiba trichistandra, Bursera graveolens and Geoffroea spinosa. According to the Shannon index, diversity is high (3.83). The diameter distribution of the individuals presented an inverted "J" pattern, indicating that the forest still conserves elements in its composition and structure from the original. The species found are representative of the dry forest with anthropic intervention of selective use and without technical planning.